2016
DOI: 10.1038/srep20992
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages programmed by apoptotic cells inhibit epithelial-mesenchymal transition in lung alveolar epithelial cells via PGE2, PGD2, and HGF

Abstract: Apoptotic cell clearance results in the release of growth factors and the action of signaling molecules involved in tissue homeostasis maintenance. Here, we investigated whether and how macrophages programmed by apoptotic cells inhibit the TGF-β1-induced Epithelial-mesenchymal transition (EMT) process in lung alveolar epithelial cells. Treatment with conditioned medium derived from macrophages exposed to apoptotic cells, but not viable or necrotic cells, inhibited TGF-β1-induced EMT, including loss of E-cadher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 62 publications
(108 reference statements)
2
42
0
Order By: Relevance
“…The inhibition of PGE formation by COX inhibition is the major mechanism of action of NSAIDs. PGE2 can inhibit TGF‐β‐induced mesenchymal epithelial transition (Yoon, Lee, Choi, Park, & Kang, ). PGE2 is associated with the suppressive effects of TGF‐β2 on the collagen degeneration in OA articular cartilage (Tchetina, Antoniou, Tanzer, Zukor, & Poole, ), and PGE2 can inhibit collagen degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of PGE formation by COX inhibition is the major mechanism of action of NSAIDs. PGE2 can inhibit TGF‐β‐induced mesenchymal epithelial transition (Yoon, Lee, Choi, Park, & Kang, ). PGE2 is associated with the suppressive effects of TGF‐β2 on the collagen degeneration in OA articular cartilage (Tchetina, Antoniou, Tanzer, Zukor, & Poole, ), and PGE2 can inhibit collagen degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that anti-fibrotic effects of apoptotic cell instillation after bleomycin treatment were significant on days 14 and 21 after BLM treatment [11, 20]. In addition, anti-EMT effect of apoptotic cell instillation on primary type II alveolar epithelial cells was determined at 14 days after BLM treatment [36]. Although fibrotic response including hydroxyproline levels at 21 days after bleomycin is greater those that at 14 days, fibrotic response day 14 after bleomycin is prominent.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the reprogramming products, such as TGFβ and arginase 1, are drivers of tissue fibrosis, while others, such as IL‐10 and 12/15‐LO metabolites limit scaring and promote restoration of normal tissue architecture and function. Intriguingly, instillation of apoptotic cells, as well as physiological neutrophil efferocytosis, seems to limit lung fibrosis by promoting macrophage reprogramming …”
Section: “Eat Me” Signals and Their Contribution To Efferocytosis Andmentioning
confidence: 99%
“…28 Some of the reprogramming products, such as TGFβ and arginase 1, are drivers of tissue fibrosis, 27 while others, such as IL-10 29,30,31 and 12/15-LO metabolites [32][33][34] limit scaring and promote restoration of normal tissue architecture and function. Intriguingly, instillation of apoptotic cells, 35,36 as well as physiological neutrophil efferocytosis, seems to limit lung fibrosis by promoting macrophage reprogramming. 37,38 Using zymosan A-initiated peritonitis, a model of spontaneously resolving inflammation, it was shown that macrophages are reprogrammed to different phenotypes following the efferocytic uptake of apoptotic neutrophils.…”
Section: Contribution To Efferocytosis and Reprogramming Of Phagocytesmentioning
confidence: 99%